1976
DOI: 10.4269/ajtmh.1976.25.108
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in Patients with Hepatosplenic Schistosomiasis Mansoni *

Abstract: In a prospective study of renal involvement in 100 consecutively hospitalized patients with hepatosplenic schistosomiasis mansoni, 15 exhibited persistent proteinuria of varying degree, which in 6 instances was accompanied by hypertension. Nine patients had the nephrotic syndrome. The most common glomerular lesion in this group was membrano-proliferative glomerulonephritis. Surgical biospy obtained during splenectomy in 15 patients without clinical evidence of renal involvement showed glomerular lesions in 6 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Patients with chronic S. mansoni infection involving portal hypertension and an enlarged spleen (hepatosplenic schistosomiasis) have an increased frequency (15%) of renal disease; this infection is clinically characterized by variable proteinuria ranging from asymptomatic to nephrotic syndrome (4,10,61). The pathological changes vary.…”
Section: Schistosoma Mansonimentioning
confidence: 99%
“…Patients with chronic S. mansoni infection involving portal hypertension and an enlarged spleen (hepatosplenic schistosomiasis) have an increased frequency (15%) of renal disease; this infection is clinically characterized by variable proteinuria ranging from asymptomatic to nephrotic syndrome (4,10,61). The pathological changes vary.…”
Section: Schistosoma Mansonimentioning
confidence: 99%
“…Studies in Brazil show that up to 15% of patients with hepatosplenic schistosomiasis also present renal disease [6][7][8][9][10][11][12][13][14] . In Egypt, Barsoum 15,16 reported that in 10% of patients on chronic hemodialysis, schistosomiasis was the primary cause of their renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…Class II (exudative glomerulonephritis) occurs in the presence of concomitant infection by Schistosoma and Salmonella species. Patients may have nephrotic or nephritic syndrome and a proliferative glomerulonephritis with neutrophil infiltration of the glomeruli (Bassily et al 1976, Rocha et al 1976, Martinelli et al 1992. Class III (membranoproliferative glomerulonephritis) and Class IV (focal segmental glomerulosclerosis) represent the patterns of glomerular lesion that are most consistently associated with the hepatosplenic form of schistosomiasis in Brazil.…”
mentioning
confidence: 99%